Motion Tracking With Web Camera Images Based On Spatial Properties - Lee, Andrew Choon Guan (2003)
Machine Vision provides a cheap and flexible mean of tracking objects in motion when implemented by a web Camera. The low resolution digital images, capturing the different instances of the scene of object in motion yields information which can be used to lay a historical track of the object. The implementation of such a system. involved the separation of the objects from the background using threshold segmentation techniques. Although it accepted the variation of natural lighting, it assumed that the background was lighter than the objects. By that method, the objects which have the potential to move, were separated from the stationary background.The segmentation scheme implemented was a robust automated scheme, and form the preprocessing stage of the whole system.